EFFECT OF MODERN MANAGEMENT ACCOUNTING PRACTICE ON LISTED CONSUMER GOODS’ COMPANIES IN NIGERIA (Journal of Contemporary Issues in Accounting, 2022)
This study aims to investigate the application of modern management accounting techniques and the challenges confronting its application in the unlisted consumer goods’ firms in Nigeria. One set of questionnaire was structured and used to gather the primary data. 56 firms representing 30% of the population were sampled and 38 of them returned the completed questionnaire. Descriptive statistics, one sample t-test and Spearman correlation were used to analyse the data. It was found out the most of the new techniques have not been known as only Total Quality Management, Customer Accounting, Throughput Accounting and Back-flush Accounting have only been partially or fully used. Lack of management support is the most prevailing challenge revealed, followed by lack of awareness of those techniques and preference for financial/historical information. The findings of this study indicates that consumer goods firms in Nigeria are still addicted to practicing management accounting techniques, though in conjunction with a few of the modern techniques. Empirical evidence from the study suggests a moderate and positive relationship between firm size and modern management accounting techniques.
Keywords: Accounting; Techniques; Application; Management; Consumers